The necessary competences in mentor's role: key to success in the induction process - Daniela MATURANA CASTILLO (Ediciones Universidad de Salamanca, 2018)
The insertion of beginner teachers in the schools is very difficult and a real challenge. The reality shock confronts and threats the teachers' identity and their stay in the scholar system. For this reason, different induction systems has emerged for the purpose to guide this difficult period in life of beginner teachers. Nevertheless, mentoring involves a very different professional expertise, with specific competences, that are not similar to necessary competences in the classroom. For this, is crucial that the mentor develops specific competences that will allow guiding the mentoring process in an effective and relevant way.